Living with leopards: an assessment of conflict and people's attitudes towards the common leopard Panthera pardus in a protected area in the Indian Himalayan region - Muzaffar A. Kichloo; Asha Sohil; Neeraj Sharma (Oryx, 2024)
Protected areas are important for wildlife conservation but they are also used by many local communities for livelihood activities. This often leads to conflicts and erodes the tolerance of local people for wildlife, particularly towards carnivores that prey on livestock. To enhance conservation success and improve the social carrying capacity of carnivores, it is essential to understand the factors influencing such conflicts and the attitudes of people interacting with carnivores. We used structured questionnaire surveys to assess the extent of livestock mortality and community responses to common leopards Panthera pardus in Kishtwar National Park, a relatively understudied protected area in the Greater Himalayan region of India. The mountainous Park and its surroundings have historically served as a haven for the local agro-pastoralists and transhumant pastoralists, resulting in complex human–wildlife interactions across the larger landscape. Our results showed that leopards were responsible for high livestock depredation (71 incidents in 2 years), and households with larger livestock holdings experienced a higher predation rate compared to those with smaller livestock holdings. An ordinal logistic regression model revealed that respondents’ age and period of activity in the Park significantly influenced their opinions regarding leopards. Large losses suffered by otherwise low-income households resulted in more negative attitudes towards these predators. Our study indicates that financial compensation for livestock losses is a key factor in improving human–leopard coexistence. A comprehensive, cross-sector collaborative approach would help to improve conflict resolution and promote favourable attitudes towards these predators.